Mechanosensitive channels in lung disease - Zheng, Mengning; Borkar, Niyati A.; Yao, Yang; Ye, Xianwei; Vogel, Elizabeth R.; Pabelick, Christina M.; Prakash, Y. S. (Frontiers in Physiology, 2023)
Mechanosensitive channels (MS channels) are membrane proteins capable of responding to mechanical stress over a wide dynamic range of external mechanical stimuli. In recent years, it has been found that MS channels play an important role as "sentinels" in the process of cell sensing and response to extracellular and intracellular force signals. There is growing appreciation for mechanical activation of ion channels and their subsequent initiation of downstream signaling pathways. Members of the transient receptor potential (TRP) superfamily and Piezo channels are broadly expressed in human tissues and contribute to multiple cellular functions. Both TRP and Piezo channels are thought to play key roles in physiological homeostasis and pathophysiology of disease states including in the lung. Here, we review the current state of knowledge on the expression, regulation, and function of TRP and Piezo channels in the context of the adult lung across the age spectrum, and in lung diseases such as asthma, COPD and pulmonary fibrosis where mechanical forces likely play varied roles in the structural and functional changes characteristic of these diseases. Understanding of TRP and Piezo in the lung can provide insights into new targets for treatment of pulmonary disease.